Tests of the different variants of the monetary model in a developing economy : Malaysian experience in the pre-and post-crisis periods. - Lee, Chin; Azali, Mohamed; M. Masih, Abul Mansur (Routledge, 2009)
This study examines the validity of four different variants of the monetary model of exchange rate determination for Malaysia covering both the pre- and post-crisis periods using the vector error-correction models. The findings demonstrate that for both periods, the variables used are cointegrated. Tests tend to suggest that of the four variants of monetary model, the sticky-price model holds in both periods and the flexible-price model holds only in the post-crisis period. The proportionality between the exchange rate and relative money does not hold in any period. The plotted actual and fitted exchange rates for both sub-samples show that the models are able to track the actual exchange rate trend quiet well.